Effect of Women's Existence in Corporate Governance and Educational Background on Company Performance - Lestari, Nanik; Sugianti, Triana Pipit (Pusat P2M Politeknik Negeri Batam, 2023)
This study aims to determine the influence of women in corporate governance and educational background on company performance. The data of this study include women (female commissioners, female directors, female audit committees), educational backgrounds (commissioners, directors, audit committees) to be independent variables, while the dependent variable is the performance of companies that use ROA. This study also uses control variables namely company size and leverage. This research data is in the form of secondary data obtained from the Indonesia Stock Exchange. Determination of the sample using the purpose sampling method and obtained as many as 2137 samples. The hypothesis in this study was multiple regression analysis. The results of this study include the first, female commissioners have negative value on the company's performance. Second, positive career women towards company performance. Third, the women's audit committee is experienced in the company's performance. Fourth, educational background Positive commitment to company performance. Fifth, the educational background is called negative towards company performance. Sixth, the background of the audit committee education does not affect the company's performance